2013
DOI: 10.1111/1460-6984.12045
|View full text |Cite
|
Sign up to set email alerts
|

Which are the best predictors of theory of mind delay in children with specific language impairment?

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 52 publications
1
24
0
2
Order By: Relevance
“…Interestingly, Farrar et al (2009) found that while syntactic complementation was not correlated with FB performance in preschoolers with SLI, general grammatical development and vocabulary were significant predictors of ToM ability. In line with this, Andrés-Roqueta et al (2013) found that, compared to age-matched control children, children with SLI showed more problems on several FB tasks; moreover, FB performance in SLI was best predicted by their overall linguistic abilities, and their grammatical abilities in particular. In another study from this group (Andrés-Roqueta et al, 2016), similar results were found; preschoolers with SLI were shown to have a significant delay both in language and performance on FB and strange stories tasks.…”
Section: Introductionmentioning
confidence: 75%
“…Interestingly, Farrar et al (2009) found that while syntactic complementation was not correlated with FB performance in preschoolers with SLI, general grammatical development and vocabulary were significant predictors of ToM ability. In line with this, Andrés-Roqueta et al (2013) found that, compared to age-matched control children, children with SLI showed more problems on several FB tasks; moreover, FB performance in SLI was best predicted by their overall linguistic abilities, and their grammatical abilities in particular. In another study from this group (Andrés-Roqueta et al, 2016), similar results were found; preschoolers with SLI were shown to have a significant delay both in language and performance on FB and strange stories tasks.…”
Section: Introductionmentioning
confidence: 75%
“…The exact mechanism through which language impairment influences ToM development in these children cannot, however, be inferred due to the lack of longitudinal investigations on this subject. Studies documenting moderate to strong associations between language and ToM within samples of children with SLI, nevertheless, support a link between these domains in this population (Andr es- Roqueta et al, 2013;Farmer, 2000;Farrar et al, 2009;Holmes, 2002;Stich, 2010). In two of these studies, specific linguistic correlates of ToM were also examined, hence informing the unsettled debate on this subject (e.g., Astington & Baird, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…In two of these studies, specific linguistic correlates of ToM were also examined, hence informing the unsettled debate on this subject (e.g., Astington & Baird, ). Regression analyses revealed that grammatical ability was the strongest linguistic predictor of ToM performance in children with SLI (Andrés‐Roqueta et al., ; Farrar et al., ). Thus, grammatical difficulties that are prevalent in SLI (Bishop, ) may be implicated in the ToM impairments of these children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…an inability to take an addressee's perspective). Further, since there is evidence to suggest that children with SLI can pass these tests of false belief by seven years of age (Andrés-Roqueta et al, 2013;Farmer, 2000), they should be within the reach of the children at the mean age of our clinical sample.…”
Section: Participants and Standardised Testsmentioning
confidence: 98%